Rough polishing pad for SiC wafer and preparation method of rough polishing pad
By combining wet resin with different hard segment contents and adding specific coupling agents and antioxidants, a rough SiC wafer pad with high hardness and strength, good wear resistance and corrosion resistance was prepared, and the existing technology was solved. The problem of insufficient performance of medium-coarse pads has achieved efficient SiC wafer rough polishing effect.
Patent Information
- Application Number
- CN202411413581.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing rough pads used for SiC wafers have disadvantages such as low hardness and strength, poor wear resistance, poor corrosion resistance, low removal rate, insufficient flatness, high surface defects and short service life in the CMP process, which is difficult to meet SiC crystals. High technical requirements for round rough polishing process.
By combining the A-type wet resin with a polyurethane-polyurea link and a high hard segment content, and a B-type wet resin with a polyurethane link and a low hard segment content, an aminosilane coupling agent and an epoxy silane are added. Coupling agent, hindered phenol antioxidant, phosphite antioxidant and diluted solvent were prepared to prepare a crude pad with high hardness and strength, good wear resistance and good corrosion resistance.
While maintaining a high removal rate and a long service life, it also takes into account the high flatness and low defects on the SiC wafer surface, improving the comprehensive polishing performance of the rough pad.
Smart Images

Figure CN119458143A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of SiC wafer polishing, and in particular relates to a rough polishing pad for SiC wafer and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) is a third-generation semiconductor material with a bandgap of 2.3eV, making it a wide-bandgap semiconductor material. Conductive SiC is mainly used in high-voltage working fields such as electric vehicles, photovoltaic power generation, and rail transportation. Among them, electric vehicles are the largest downstream market for third-generation semiconductor materials.
[0003] One of the key links in the SiC substrate processing process is grinding and polishing, which mainly includes four processes: rough grinding, fine grinding, rough polishing and fine polishing. Each process needs to be adapted to different types of polishing pads and polishing liquids. In recent years, as the demand of the electric vehicle industry and its device market has become more urgent, the consumption of rough polishing pads used for SiC wafers in the CMP process has also increased. However, most domestic SiC wafer factories mainly use imported rough polishing pads. Domestic rough polishing pads generally have disadvantages such as low hardness and strength, poor wear resistance, poor corrosion resistance, low removal rate, insufficient flatness, high surface defects and short service life in the CMP process.
[0004] Most of the rough polishing pads currently available on the market for SiC wafers are made of a single wet resin, and their comprehensive polishing performance often compromises performance, and they cannot take into account a good balance in terms of service life, removal rate and flattening, degree of defects, and other performances, making it difficult to meet the high technical requirements of the SiC wafer rough polishing process. For example, some rough polishing pads have high hardness and strength, and show good wear resistance and corrosion resistance in the rough polishing process of SiC wafers, but will lead to insufficient flatness of the SiC wafer surface and increased defects; another part of the rough polishing pads have good flexibility and compressibility, and show high flatness and low defectivity in the rough polishing process of SiC wafers, but their wear resistance and corrosion resistance are poor, resulting in a short service life and low removal rate.
[0005] Therefore, there is an urgent need to develop a rough polishing pad with excellent comprehensive performance such as high hardness and strength, good wear resistance, good corrosion resistance, high removal rate, good flatness, low defect degree, and long service life, so as to solve the problem that the existing polishing pads for SiC wafers cannot take into account comprehensive performance in many aspects. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention provides a rough polishing pad for SiC wafers, which is compounded with a type A wet resin having a polyurethane-polyurea chain and a high hard segment content, and a type B wet resin having a polyurethane chain and a low hard segment content, so that the physical and chemical properties are synergistically complementary, thereby improving the comprehensive polishing performance of the rough polishing pad. The prepared rough polishing pad has the advantages of high hardness, good wear resistance, and good corrosion resistance. While maintaining a high removal rate and a long service life, the surface of the SiC wafer has a high flatness and a low defectivity. The present invention also provides a preparation method of the rough polishing pad.
[0007] The technical effects to be achieved by the present invention are achieved through the following technical aspects:
[0008] In a first aspect, the present invention provides a rough polishing pad for SiC wafers, which is prepared from the following components in parts by weight:
[0009] 500-1500 parts of A-type wet resin, 200-800 parts of B-type wet resin, 5-10 parts of aminosilane coupling agent, 5-10 parts of epoxysilane coupling agent, 1-5 parts of hindered phenol antioxidant, 1-5 parts of phosphite antioxidant, 600-1600 parts of diluent solvent, 150-160 parts of non-woven fabric, 300-330 parts of adhesive;
[0010] The type A wet-process resin is a wet-process resin having polyurethane-polyurea chain segments and a hard segment content of 54.5% to 66.7%; the type B wet-process resin is a wet-process resin having polyurethane chain segments and a hard segment content of 35.1% to 45.8%.
[0011] In some embodiments, the rough polishing pad for SiC wafer has a thickness of 1.2 to 1.4 mm, a hardness of 75 to 85 Shore A, and a compression ratio of 2% to 5%;
[0012] The viscosity of the type A wet-process resin at 25° C. is 100,000 to 120,000 mPa·S, and the number average molecular weight Mn is 80,000 to 100,000;
[0013] The B-type wet-process resin has a viscosity of 80,000 to 100,000 mPa·S at 25° C. and a number average molecular weight Mn of 60,000 to 80,000.
[0014] In some embodiments, the aminosilane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane;
[0015] The epoxysilane coupling agent is selected from at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(2,3-epoxypropoxy)propyltriethoxysilane.
[0016] In some embodiments, the hindered phenol antioxidant is selected from at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, or 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene;
[0017] The phosphite antioxidant is selected from at least one of tris(2,4-di-tert-butyl)phenyl phosphite, triphenyl phosphite or tris(nonylphenol)phosphite.
[0018] In some embodiments, the dilution solvent is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide;
[0019] The nonwoven fabric is selected from PET needle-punched nonwoven fabric or PET spunlace nonwoven fabric, and its thickness is between 1.3 and 1.5 mm, and its gram weight is between 150 and 160 g / m 2 between.
[0020] The back adhesive is selected from pressure-sensitive acrylic or silicone double-sided adhesive, and its thickness is between 100 and 200 μm.
[0021] In some embodiments, the A-type wet-process resin is prepared from the following components in parts by weight:
[0022] 150-200 parts of diisocyanate, 200-250 parts of polyether diol, 150-200 parts of aromatic diamine, 1-5 parts of chain terminator, and 500-1500 parts of diluent solvent.
[0023] In some embodiments, the diisocyanate is selected from at least one of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 4,4'-diphenylmethane diisocyanate or 2,4'-diphenylmethane diisocyanate;
[0024] The polyether diol is selected from at least one of polypropylene glycol, polytrimethylene ether glycol or polytetrahydrofuran diol;
[0025] The aromatic diamine is selected from at least one of 4,4'-diamino-3,3'-dichlorodiphenylmethane, diethyltoluenediamine or 4,4'-methylenebis(3-chloro-2,6-diethylaniline);
[0026] The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
[0027] In some embodiments, the method for synthesizing the type A wet resin comprises the following steps:
[0028] Prepolymerization reaction: dehydrating the polyether diol at 105-110° C. and negative pressure of 0.08-0.10 MPa for 1 hour, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0029] Chain extension reaction: adding diluent solvent and aromatic diamine to the prepared prepolymer in sequence for chain extension, and maintaining the temperature between 80 and 90° C. for solution polymerization reaction for 4 to 6 hours;
[0030] The reaction is terminated. When the polymerization reaction of the above system reaches a number average molecular weight Mn between 80,000 and 100,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a type A wet-process resin.
[0031] In some embodiments, the B-type wet-process resin is prepared from the following components in parts by weight:
[0032] 250-300 parts of diisocyanate, 450-500 parts of polyester diol, 20-80 parts of small molecule diol, 1-3 parts of chain terminator, and 1000-2000 parts of diluent.
[0033] In some embodiments, the diisocyanate is selected from at least one of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 4,4'-diphenylmethane diisocyanate or 2,4'-diphenylmethane diisocyanate;
[0034] The polyester diol is selected from at least one of polycaprolactone diol and polycarbonate diol;
[0035] The small molecule diol is selected from at least one of ethylene glycol, 1,4-butanediol or 1,3-propylene glycol;
[0036] The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
[0037] In some embodiments, the method for synthesizing the type B wet process resin comprises the following steps:
[0038] Prepolymerization reaction: dehydrating the polyester diol at 110-115° C. and negative pressure of 0.08-0.10 MPa for 2 hours, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0039] Chain extension reaction: adding diluent solvent and small molecule diol to the prepared prepolymer in sequence for chain extension, and maintaining the solution polymerization reaction at 80-90°C for 4-6 hours;
[0040] The reaction is terminated. When the polymerization reaction of the above system reaches a number average molecular weight Mn between 60,000 and 80,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a B-type wet-process resin.
[0041] In a second aspect, the present invention provides a method for preparing a rough polishing pad, which is used to prepare the rough polishing pad for SiC wafers, and the preparation method comprises the following steps:
[0042] Step 1: Impregnation slurry dispersion, add type A wet resin, type B wet resin, amino silane coupling agent, epoxy silane coupling agent, hindered phenol antioxidant, phosphite antioxidant and dilution solvent into a container, and disperse at a speed of 800-1000r / min for 2-3h until the mixture is evenly mixed;
[0043] Step 2: Degassing the impregnation slurry, degassing the evenly dispersed impregnation slurry for 2 to 3 hours under a negative pressure of 0.08 to 0.10 MPa, and the viscosity of the impregnation slurry at 25° C. is 1000 to 3000 mPa·S;
[0044] Step 3: impregnation and wet coagulation, the impregnation slurry and the non-woven fabric fiber are fully mixed to make the impregnation uniform, and placed in a DMF aqueous solution with a temperature of 25 to 45° C. and a concentration of 10% to 30% for wet coagulation;
[0045] Step 4: Washing and drying to fix the solidified sample, place the solidified sample in deionized water at 40-60°C to clean the solvent, repeat more than 10 times until the sample solvent concentration is less than 1%, and place it at 100-120°C to dry for 4-6 hours to fix the sample;
[0046] Step 5: Surface grinding and grooving: Grind the above-shaped sample with 150-400 grit sandpaper to make it smooth, remove the wet resin attached to the surface, and then perform grooving;
[0047] Step 6: Back glue bonding and cutting, the above-mentioned grooved samples are bonded with back glue and cut into discs to obtain rough polishing pads for SiC wafers.
[0048] In summary, the present invention has at least the following benefits:
[0049] 1. The rough polishing pad for SiC wafer provided by the present invention is compounded with a type A wet resin having a polyurethane-polyurea chain and a high hard segment content, and a type B wet resin having a polyurethane chain and a low hard segment content, so that the physical and chemical properties of the resins are synergistically complementary, thereby improving the comprehensive polishing performance of the rough polishing pad; compared with the rough polishing pad product using a single wet resin, the rough polishing pad prepared by the present invention has the advantages of high hardness and strength, good wear resistance, and good corrosion resistance. While maintaining a high removal rate and a long service life, it also takes into account that the surface of the SiC wafer has a high flatness and a low defectivity.
[0050] 2. The preparation method of the rough polishing pad provided by the present invention, on the one hand, the silane coupling agent added in the wet impregnation process can react with water molecules to produce silanol groups during the solidification process, and produce hydrogen bonds with the wet resin and the PET fiber interface, which can greatly improve the binding force and adhesion between the PET fiber and the wet resin. In the rough polishing process of the SiC wafer, the wet resin and the PET fiber are more tightly combined and not easy to fall off, thereby improving the wear resistance, so that the prepared rough polishing pad has a higher removal rate and a longer service life; on the other hand, the composite antioxidant added in the wet impregnation process can greatly improve the tolerance of the prepared rough polishing pad to the oxidant in the polishing liquid. In the rough polishing process of the SiC wafer, the prepared rough polishing pad is not easily oxidized by the polishing liquid and the wet resin is not easy to fall off, and the corrosion resistance and service life of the rough polishing pad can also be synergistically improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The present invention is a simplified flow chart of the method for preparing the rough polishing pad according to Example 1.
[0052] Figure 2 This is a surface SEM image of the rough polishing pad for SiC wafer prepared in Example 1 of the present invention.
[0053] Figure 3 This is a cross-sectional SEM image of the rough polishing pad for SiC wafer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0054] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with the accompanying drawings and specific embodiments. Preferred embodiments of the present invention are provided in the embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0056] References in the specification to "one embodiment", "embodiment", "exemplary embodiment", etc. mean the embodiment being described, but not every embodiment may include a particular feature, structure, or characteristic. Specific features, structures, or characteristics are included. Moreover, such phrases do not necessarily refer to the same embodiment. In addition, when specific features, structures, or characteristics are described in conjunction with certain embodiments, whether or not explicitly described, it is within the knowledge of those skilled in the art to consider the effects of applying the features, structures, or characteristics to other embodiments.
[0057] The values expressed as ranges should be interpreted in a flexible manner, including not only the values explicitly listed as the limits of the range, but also all individual values or sub-ranges included in the range, as if each value and sub-range were clearly stated. For example, a (mass) concentration range of "about 0.1% to about 5%" should be interpreted as including not only the explicitly listed values of about 0.1% to about 5% by weight, but also the individual (mass) concentrations (e.g., 1%, 2%, 3% and 4%) and sub-ranges (e.g., 0.1% to 0.5%, 1.1% to 2.2% and 3.3% to 4.4%) within the specified range.
[0058] As described herein, unless stated otherwise, the terms "a" and "an" are used to include one or more than one, and the term "or" is used to refer to a non-exclusive "or". In addition, when a term or terms used herein are not otherwise qualified, they should be understood to be used for descriptive purposes only and not for limiting purposes. In addition, all publications, patents, and patent documents mentioned in the specification are incorporated herein by reference in their entirety, as if individually incorporated by introduction. If there is an inconsistency in usage between this document and those documents incorporated by reference, the usage in the cited references should be considered to supplement this document. For irreconcilable inconsistencies, the usage in this document shall prevail.
[0059] A rough polishing pad for SiC wafers is prepared from the following components in parts by weight:
[0060] 500-1500 parts of A-type wet resin, 200-800 parts of B-type wet resin, 5-10 parts of aminosilane coupling agent, 5-10 parts of epoxysilane coupling agent, 1-5 parts of hindered phenol antioxidant, 1-5 parts of phosphite antioxidant, 600-1600 parts of diluent solvent, 150-160 parts of non-woven fabric, 300-330 parts of adhesive;
[0061] Among them, the type A wet-process resin is a wet-process resin with polyurethane-polyurea chain segments and a hard segment content of 54.5% to 66.7%; the type B wet-process resin is a wet-process resin with polyurethane chain segments and a hard segment content of 35.1% to 45.8%.
[0062] The rough polishing pad used for SiC wafers has a thickness of 1.2 to 1.4 mm, a hardness of 75 to 85 Shore A, and a compression ratio of 2% to 5%;
[0063] The viscosity of type A wet-process resin at 25°C is 100,000 to 120,000 mPa·S, and the number average molecular weight Mn is 80,000 to 100,000;
[0064] The viscosity of the B-type wet-process resin at 25° C. is 80,000 to 100,000 mPa·S, and the number average molecular weight Mn is 60,000 to 80,000.
[0065] Further, the aminosilane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane (KH-550) or 3-aminopropyltrimethoxysilane (KH-540);
[0066] The epoxysilane coupling agent is selected from at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560) and 3-(2,3-epoxypropoxy)propyltriethoxysilane (KH-561).
[0067] Further, the hindered phenol antioxidant is selected from at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Antioxidant 1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester (Antioxidant 1076) or 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Antioxidant 1330);
[0068] The phosphite antioxidant is selected from at least one of tris(2,4-di-tert-butyl)phenyl phosphite (Antioxidant 168), triphenyl phosphite (TPP) or tris(nonylphenol)phosphite (TNP).
[0069] Further, the diluting solvent is selected from N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO);
[0070] The non-woven fabric is selected from PET needle-punched non-woven fabric or PET spunlace non-woven fabric, with a thickness of 1.3-1.5 mm and a gram weight of 150-160 g / m 2 between.
[0071] The back adhesive is selected from pressure-sensitive acrylic or silicone double-sided adhesive, and its thickness is between 100 and 200 μm.
[0072] Furthermore, the A-type wet-process resin is prepared from the following components in parts by weight:
[0073] 150-200 parts of diisocyanate, 200-250 parts of polyether diol, 150-200 parts of aromatic diamine, 1-5 parts of chain terminator, and 500-1500 parts of diluent solvent.
[0074] Further, the diisocyanate is selected from at least one of toluene-2,4-diisocyanate (2,4-TDI), toluene-2,6-diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4-MDI) or 2,4'-diphenylmethane diisocyanate (2,4-MDI);
[0075] The polyether diol is selected from at least one of polypropylene glycol, polytrimethylene ether glycol or polytetramethylene glycol; wherein polypropylene glycol is preferably PPG-1000, PPG-2000, PPG-3000; polytrimethylene ether glycol is preferably PO3G-1000, PO3G-2000, PO3G-3000; polytetramethylene glycol is preferably PTMG-1000, PTMG-2000, PTMG-3000.
[0076] The aromatic diamine is at least one selected from 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), diethyltoluenediamine (DETDA), and 4,4'-methylenebis(3-chloro-2,6-diethylaniline) (MCDEA);
[0077] The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
[0078] The synthesis method of type A wet resin comprises the following steps:
[0079] Step 1, prepolymerization reaction, dehydrating the polyether diol at 105-110° C. and negative pressure of 0.08-0.10 MPa for 1 hour, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0080] Step 2: Chain extension reaction: adding a diluent solvent and an aromatic diamine to the obtained prepolymer in sequence for chain extension, and maintaining the temperature between 80 and 90° C. for solution polymerization reaction for 4 to 6 hours;
[0081] Step 3: Termination of the reaction: When the polymerization reaction of the above system reaches a number average molecular weight Mn between 80,000 and 100,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a type A wet process resin.
[0082] Type B wet process resin is prepared from the following components in parts by weight:
[0083] 250-300 parts of diisocyanate, 450-500 parts of polyester diol, 20-80 parts of small molecule diol, 1-3 parts of chain terminator, and 1000-2000 parts of diluent.
[0084] The diisocyanate is selected from at least one of toluene-2,4-diisocyanate (2,4-TDI), toluene-2,6-diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4-MDI) or 2,4'-diphenylmethane diisocyanate (2,4-MDI);
[0085] The polyester diol is selected from at least one of polycaprolactone diol and polycarbonate diol; wherein the polycaprolactone diol is preferably PCL-1000, PCL-2000, PCL-3000, and the polycarbonate diol is preferably PCDL-1000, PCDL-2000, PCDL-3000;
[0086] The small molecule diol is selected from at least one of ethylene glycol (EG), 1,4-butanediol (BG) or 1,3-propylene glycol (PG);
[0087] The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
[0088] The synthesis method of type B wet resin comprises the following steps:
[0089] Step 1, prepolymerization reaction, dehydrating the polyester diol at 110-115° C. and negative pressure of 0.08-0.10 MPa for 2 hours, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0090] Step 2: Chain extension reaction: adding diluent solvent and small molecule diol to the obtained prepolymer in sequence for chain extension, and maintaining the solution polymerization reaction at 80-90° C. for 4-6 hours;
[0091] Step 3, termination reaction: when the above system is polymerized to a number average molecular weight Mn between 60,000 and 80,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a B-type wet process resin.
[0092] The rough polishing pad provided by the embodiment of the present invention has the advantages of high hardness, good wear resistance and good corrosion resistance. It has strong tolerance to the oxidant in the rough polishing liquid in the rough polishing process of the SiC wafer, and the wet resin is tightly combined with the non-woven fabric fiber and is not easy to fall off. While maintaining a high removal rate and a long service life, it can also take into account the high flatness and low defect level of the SiC wafer surface.
[0093] The rough polishing pad for SiC wafer is prepared by the following preparation method, which specifically comprises the following steps:
[0094] Step 1: Impregnation slurry dispersion, add type A wet resin, type B wet resin, amino silane coupling agent, epoxy silane coupling agent, hindered phenol antioxidant, phosphite antioxidant and dilution solvent into a container, and disperse at a speed of 800-1000r / min for 2-3h until the mixture is evenly mixed;
[0095] Regarding the synthesis methods of Type A wet process resin and Type B wet process resin, please see the above description.
[0096] Step 2: Degassing the impregnation slurry, degassing the evenly dispersed impregnation slurry for 2 to 3 hours under a negative pressure of 0.08 to 0.10 MPa, and the viscosity of the impregnation slurry at 25° C. is 1000 to 3000 mPa·S;
[0097] Step 3: impregnation and wet coagulation, the impregnation slurry and the non-woven fabric fiber are fully mixed to make the impregnation uniform, and placed in a DMF aqueous solution with a temperature of 25 to 45° C. and a concentration of 10% to 30% for wet coagulation;
[0098] Step 4: Washing and drying to fix the solidified sample, place the solidified sample in deionized water at 40-60°C to clean the solvent, repeat more than 10 times until the sample solvent concentration is less than 1%, and place it at 100-120°C to dry for 4-6 hours to fix the sample;
[0099] Step 5: Surface grinding and grooving: Grind the above-shaped sample with 150-400 grit sandpaper to make it smooth, remove the wet resin attached to the surface, and then perform grooving;
[0100] Step 6: Back glue bonding and cutting, the above-mentioned grooved samples are bonded with back glue and cut into discs to obtain rough polishing pads for SiC wafers.
[0101] The rough polishing pad for SiC wafer is prepared by the above preparation method. The preparation method comprises the following steps: synthesizing type A wet resin and type B wet resin with different material chain links and hard segment contents, compounding type A wet resin and type B wet resin, adding coupling agent, antioxidant and diluent to mix and disperse the mixture evenly to prepare an impregnation slurry, fully mixing and impregnating the mixture evenly with non-woven fabric fibers after vacuum degassing, solidifying, washing, drying, grinding and grooving, and finally pasting a backing adhesive and cutting the mixture into wafers to obtain a rough polishing pad for SiC wafer.
[0102] Example 1
[0103] The present embodiment provides a rough polishing pad for SiC wafers, which is prepared from the following components by weight: 1000 parts of A-type wet resin, 500 parts of B-type wet resin, 8 parts of aminosilane coupling agent, 7 parts of epoxysilane coupling agent, 3 parts of hindered phenol antioxidant, 2 parts of phosphite antioxidant, 1100 parts of diluent, 155 parts of non-woven fabric, and 315 parts of adhesive. The rough polishing pad has a thickness of 1.3 mm, a hardness of 80 Shore A, and a compression ratio of 3.5%.
[0104] In this embodiment, the type A wet resin is a wet resin having polyurethane-polyurea chain segments, a hard segment content of 60.3%, a viscosity of 112500 mPa·S at 25° C., and a number average molecular weight Mn of 92800;
[0105] The B-type wet resin is a wet resin having polyurethane chain segments, a hard segment content of 40.7%, a viscosity of 96,300 mPa·S at 25° C., and a number average molecular weight Mn of 71,700.
[0106] Preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane (KH-550), the epoxysilane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), the hindered phenol antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (Antioxidant 1010), the phosphite antioxidant is tris(2,4-di-tert-butyl)phenyl phosphite (Antioxidant 168), the diluent is N,N-dimethylformamide (DMF), the non-woven fabric is PET needle-punched non-woven fabric, the thickness is 1.4 mm, and the weight is 155 g / m 2 The backing adhesive is a pressure-sensitive acrylic double-sided adhesive with a thickness of 150μm.
[0107] In this embodiment, the type A wet-process resin is prepared from the following components in parts by weight: 180 parts of diisocyanate, 230 parts of polyether diol, 170 parts of aromatic diamine, 3 parts of chain terminator, and 1000 parts of diluent.
[0108] Preferably, the diisocyanate is toluene-2,4-diisocyanate (2,4-TDI), the polyether diol is polypropylene glycol (preferably PPG-1000), the aromatic diamine is 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), and the chain terminator is methanol.
[0109] The synthesis method of the A-type wet resin comprises the following steps:
[0110] Step 1, prepolymerization reaction, dehydrating the polyether diol at 105-110° C. and negative pressure of 0.08-0.10 MPa for 1 hour, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0111] Step 2: Chain extension reaction: adding a diluent solvent and an aromatic diamine to the obtained prepolymer in sequence for chain extension, and maintaining the temperature between 80 and 90° C. for solution polymerization reaction for 4 to 6 hours;
[0112] Step 3: Termination of the reaction: When the polymerization reaction of the above system reaches a number average molecular weight Mn between 80,000 and 100,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a type A wet process resin.
[0113] In this embodiment, the B-type wet-process resin is prepared from the following components in parts by weight: 280 parts of diisocyanate, 480 parts of polyester diol, 50 parts of small molecule diol, 2 parts of chain terminator, and 1500 parts of diluent.
[0114] Preferably, the diisocyanate is 4,4'-diphenylmethane diisocyanate (4,4-MDI), the polyester diol is polycaprolactone diol (preferably PCL-2000), the small molecule diol is 1,4-butanediol (BG), and the chain terminator is ethanol.
[0115] The synthesis method of the B-type wet resin comprises the following steps:
[0116] Step 1, prepolymerization reaction, dehydrating the polyester diol at 110-115° C. and negative pressure of 0.08-0.10 MPa for 2 hours, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer;
[0117] Step 2: Chain extension reaction: adding diluent solvent and small molecule diol to the obtained prepolymer in sequence for chain extension, and maintaining the solution polymerization reaction at 80-90° C. for 4-6 hours;
[0118] Step 3, termination reaction: when the above system is polymerized to a number average molecular weight Mn between 60,000 and 80,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a B-type wet process resin.
[0119] The rough polishing pad for SiC wafer is prepared by the following preparation method, referring to Figure 1 , specifically including the following steps:
[0120] Step 1: Impregnation slurry dispersion, add type A wet resin, type B wet resin, amino silane coupling agent, epoxy silane coupling agent, hindered phenol antioxidant, phosphite antioxidant and dilution solvent into a container, and disperse at a speed of 800-1000r / min for 2-3h until the mixture is evenly mixed;
[0121] Step 2: Degassing the impregnation slurry, degassing the evenly dispersed impregnation slurry for 2 to 3 hours under a negative pressure of 0.08 to 0.10 MPa, and the viscosity of the impregnation slurry at 25° C. is 1000 to 3000 mPa·S;
[0122] Step 3: impregnation and wet coagulation, the impregnation slurry and the non-woven fabric fiber are fully mixed to make the impregnation uniform, and placed in a DMF aqueous solution with a temperature of 25 to 45° C. and a concentration of 10% to 30% for wet coagulation;
[0123] Step 4: Washing and drying to fix the solidified sample, place the solidified sample in deionized water at 40-60°C to clean the solvent, repeat more than 10 times until the sample solvent concentration is less than 1%, and place it at 100-120°C to dry for 4-6 hours to fix the sample;
[0124] Step 5: Surface grinding and grooving: Grind the above-shaped sample with 150-400 grit sandpaper to make it smooth, remove the wet resin attached to the surface, and then perform grooving;
[0125] Step 6: Back glue bonding and cutting, the above-mentioned grooved samples are bonded with back glue and cut into discs to obtain rough polishing pads for SiC wafers.
[0126] The surface SEM image and cross-sectional SEM image of the rough polishing pad for SiC wafer prepared in this embodiment are respectively Figure 2 and Figure 3 .
[0127] Example 2
[0128] This embodiment provides a rough polishing pad for SiC wafers, which is prepared from the following components by weight: 500 parts of A-type wet resin, 200 parts of B-type wet resin, 5 parts of aminosilane coupling agent, 5 parts of epoxysilane coupling agent, 1 part of hindered phenol antioxidant, 1 part of phosphite antioxidant, 600 parts of diluent solvent, 150 parts of non-woven fabric, and 300 parts of adhesive. The rough polishing pad has a thickness of 1.2 mm, a hardness of 75 Shore A, and a compression ratio of 5.0%.
[0129] In this embodiment, the type A wet resin is a wet resin having polyurethane-polyurea chain segments, a hard segment content of 54.5%, a viscosity of 120,000 mPa·S at 25° C., and a number average molecular weight Mn of 100,000;
[0130] The B-type wet resin is a wet resin having polyurethane chain segments, a hard segment content of 35.1%, a viscosity of 100,000 mPa·S at 25° C., and a number average molecular weight Mn of 80,000.
[0131] Preferably, the aminosilane coupling agent is 3-aminopropyltrimethoxysilane (KH-540), the epoxysilane coupling agent is 3-(2,3-epoxypropoxy)propyltriethoxysilane (KH-561), the hindered phenol antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Antioxidant 1076), the phosphite antioxidant is triphenyl phosphite (TPP), the diluent is N-methylpyrrolidone (NMP), the non-woven fabric is PET spunlace non-woven fabric, the thickness is 1.3 mm, and the weight is 150 g / m 2 The backing adhesive is a pressure-sensitive silicone double-sided adhesive with a thickness of 100μm.
[0132] In this embodiment, the type A wet-process resin is prepared from the following components in parts by weight: 150 parts of diisocyanate, 250 parts of polyether diol, 150 parts of aromatic diamine, 1 part of chain terminator, and 500 parts of diluent.
[0133] Preferably, the diisocyanate is toluene-2,6-diisocyanate (2,6-TDI), the polyether diol is polytrimethylene ether glycol (preferably PO3G-3000), the aromatic diamine is diethyltoluenediamine (DETDA), and the chain terminator is ethanol.
[0134] The synthesis method of the A-type wet resin is the same as that of Example 1.
[0135] In this embodiment, the B-type wet-process resin is prepared from the following components in parts by weight: 250 parts of diisocyanate, 500 parts of polyester diol, 20 parts of small molecule diol, 1 part of chain terminator, and 1000 parts of diluent.
[0136] Preferably, the diisocyanate is 2,4'-diphenylmethane diisocyanate (2,4-MDI), the polyester diol is polycarbonate diol (preferably PCDL-1000), the small molecule diol is ethylene glycol (EG), and the chain terminator is isopropanol.
[0137] The synthesis method of the B-type wet resin is the same as that of Example 1.
[0138] The preparation method of the rough polishing pad for SiC wafer in this embodiment is the same as that in Embodiment 1. In the preparation process, the raw materials required for each step are calculated according to the weight parts of this embodiment.
[0139] Example 3
[0140] The present embodiment provides a rough polishing pad for SiC wafers, which is prepared from the following components by weight: 1500 parts of A-type wet resin, 800 parts of B-type wet resin, 10 parts of aminosilane coupling agent, 10 parts of epoxysilane coupling agent, 5 parts of hindered phenol antioxidant, 5 parts of phosphite antioxidant, 1600 parts of diluent, 160 parts of non-woven fabric, and 330 parts of adhesive. The rough polishing pad has a thickness of 1.4 mm, a hardness of 85 Shore A, and a compression ratio of 2.0%.
[0141] In this embodiment, the type A wet resin is a wet resin having polyurethane-polyurea chain segments, a hard segment content of 66.7%, a viscosity of 100,000 mPa·S at 25° C., and a number average molecular weight Mn of 80,000;
[0142] The B-type wet-process resin is a wet-process resin having polyurethane chain segments, a hard segment content of 45.8%, a viscosity of 80,000 mPa·S at 25° C., and a number average molecular weight Mn of 60,000.
[0143] Preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane (KH-550), the epoxysilane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), the hindered phenol antioxidant is 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Antioxidant 1330), the phosphite antioxidant is tris(nonylphenol)phosphite (TNP), the diluent is dimethyl sulfoxide (DMSO), the non-woven fabric is PET needle-punched non-woven fabric, the thickness is 1.5 mm, and the weight is 160 g / m 2 The backing adhesive is a pressure-sensitive acrylic double-sided adhesive with a thickness of 200μm.
[0144] In this embodiment, the type A wet-process resin is prepared from the following components in parts by weight: 200 parts of diisocyanate, 200 parts of polyether diol, 200 parts of aromatic diamine, 5 parts of chain terminator, and 1500 parts of diluent.
[0145] Preferably, the diisocyanate is 4,4'-diphenylmethane diisocyanate (4,4-MDI), the polyether diol is polytetramethylene glycol (preferably PTMG-2000), the aromatic diamine is 4,4'-methylenebis(3-chloro-2,6-diethylaniline) (MCDEA), and the chain terminator is isopropanol.
[0146] The synthesis method of the A-type wet resin is the same as that of Example 1.
[0147] In this embodiment, the B-type wet-process resin is prepared from the following components in parts by weight: 300 parts of diisocyanate, 450 parts of polyester diol, 80 parts of small molecule diol, 3 parts of chain terminator, and 2000 parts of diluent.
[0148] Preferably, the diisocyanate is toluene-2,6-diisocyanate (2,6-TDI), the polyester diol is polycaprolactone diol (preferably PCL-3000), the small molecule diol is 1,3-propylene glycol (PG), and the chain terminator is methanol.
[0149] The synthesis method of the B-type wet resin is the same as that of Example 1.
[0150] The preparation method of the rough polishing pad for SiC wafer in this embodiment is the same as that in Embodiment 1. In the preparation process, the raw materials required for each step are calculated according to the weight parts of this embodiment.
[0151] Example 4
[0152] The present embodiment provides a rough polishing pad for SiC wafers, which is prepared from the following components by weight: 1200 parts of A-type wet resin, 600 parts of B-type wet resin, 7 parts of aminosilane coupling agent, 8 parts of epoxysilane coupling agent, 2 parts of hindered phenol antioxidant, 3 parts of phosphite antioxidant, 1000 parts of diluent, 155 parts of non-woven fabric, and 315 parts of adhesive. The rough polishing pad has a thickness of 1.3 mm, a hardness of 79 Shore A, and a compression ratio of 4.3%.
[0153] In this embodiment, the type A wet resin is a wet resin having polyurethane-polyurea chain segments, a hard segment content of 61.4%, a viscosity of 114560 mPa·S at 25° C., and a number average molecular weight Mn of 91830;
[0154] The B-type wet-process resin is a wet-process resin having polyurethane chain segments, a hard segment content of 41.3%, a viscosity of 97,600 mPa·S at 25° C., and a number average molecular weight Mn of 73,590.
[0155] Preferably, the aminosilane coupling agent is 3-aminopropyltrimethoxysilane (KH-540), the epoxysilane coupling agent is 3-(2,3-epoxypropoxy)propyltriethoxysilane (KH-561), the hindered phenol antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Antioxidant 1076), the phosphite antioxidant is triphenyl phosphite (TPP), the diluent is N,N-dimethylformamide (DMF), the non-woven fabric is PET spunlace non-woven fabric, the thickness is 1.4 mm, and the weight is 155 g / m 2The backing adhesive is a pressure-sensitive silicone double-sided adhesive with a thickness of 150μm.
[0156] In this embodiment, the type A wet-process resin is prepared from the following components by weight: 170 parts of diisocyanate, 220 parts of polyether diol, 180 parts of aromatic diamine, 2 parts of chain terminator, and 1000 parts of diluent.
[0157] Preferably, the diisocyanate is 2,4'-diphenylmethane diisocyanate (2,4-MDI), the polyether diol is polytrimethylene ether diol (preferably PO3G-2000), the aromatic diamine is 4,4'-diamino-3,3'-dichlorodiphenylmethane (MOCA), and the chain terminator is ethanol.
[0158] The synthesis method of the A-type wet resin is the same as that of Example 1.
[0159] In this embodiment, the B-type wet-process resin is prepared from the following components in parts by weight: 270 parts of diisocyanate, 470 parts of polyester diol, 60 parts of small molecule diol, 2 parts of chain terminator, and 1400 parts of diluent.
[0160] Preferably, the diisocyanate is toluene-2,4-diisocyanate (2,4-TDI), the polyester diol is polycarbonate diol (preferably PCDL-3000), the small molecule diol is 1,4-butanediol (BG), and the chain terminator is isopropanol.
[0161] The synthesis method of the B-type wet resin is the same as that of Example 1.
[0162] The preparation method of the rough polishing pad for SiC wafer in this embodiment is the same as that in Embodiment 1. In the preparation process, the raw materials required for each step are calculated according to the weight parts of this embodiment.
[0163] Comparative Example 1
[0164] The difference between Comparative Example 1 and Example 1 is that equal parts by weight of Type B wet-process resin are replaced by Type A wet-process resin, and the rest are the same as in Example 1.
[0165] Comparative Example 2
[0166] The difference between Comparative Example 2 and Example 1 is that equal parts by weight of Type A wet-process resin are replaced by Type B wet-process resin, and the rest are the same as in Example 1.
[0167] Comparative Example 3
[0168] The difference between Comparative Example 3 and Example 1 is that the weight portion of the aminosilane coupling agent is 0 part, the weight portion of the epoxysilane coupling agent is 0 part, and the rest is consistent with Example 1.
[0169] Comparative Example 4
[0170] The difference between Comparative Example 4 and Example 1 is that the weight portion of the hindered phenol antioxidant is 0 part, the weight portion of the phosphite antioxidant is 0 part, and the rest is consistent with Example 1.
[0171] Test example
[0172] The physical parameters and polishing performance of the rough polishing pads for SiC wafers prepared in Examples 1 to 4 and the rough polishing pads prepared in Comparative Examples 1 to 4 were tested.
[0173] The test method of number average molecular weight Mn refers to the national standard "GB / T 27843-2011", and the gel permeation chromatograph (GPC) model is Agilent 1260Infinity II.
[0174] The test method of tensile strength refers to the national standard "GB / T 1040.3-2006", and the electronic universal material testing machine model is ZwickRoll 5kN Allround table top.
[0175] The hardness test method refers to the national standard "GB / T 2411-2008", and the Shore A hardness tester model is Teclock GS-709G.
[0176] The test method for compression ratio refers to GB / T 30709-2014, and the dynamic thermomechanical analyzer (DMA) model is TADMA850.
[0177] The test method for wear resistance refers to GB / T 5478-2008, and the abrasion testing machine model is Taber 1700.
[0178] The corrosion resistance test method is as follows: place the sample to be tested in a mixed aqueous solution of potassium permanganate and sulfuric acid (10 wt % potassium permanganate, 10 wt % sulfuric acid, 80 wt % deionized water) until the sample falls off or breaks for a maximum time.
[0179] The test methods for polishing removal rate, life time, surface roughness and surface defects are as follows:
[0180] Remove the release paper from the 24-inch rough polishing pad sample and stick it on a high-precision surface polishing machine. The polishing liquid model is SC-A1, the flow rate is 30cc / min, the wafer model is 6-inch 4H-SiC Wafer (Si surface fine grinding), the high-precision surface polishing machine model is YM-610SP, the pressure is 2.5psi, the grinding disc speed is 30rpm (the workpiece is placed on the grinding disc and rotates), and the dressing disc is a diamond disk;
[0181] Polishing removal rate (Removal Rate) is the average value calculated by recording the removal rate during the polishing process using an optical film thickness meter (KLA Filmetrics F50);
[0182] Surface roughness (Roughness) was measured by a 3D surface profiler (CHOTEST Superview W1);
[0183] The number of surface defects is the total number of defects (including particles, scratches, protrusions, pits, etc.) on the surface of SiC wafers with a size greater than 100nm detected by surface defect detection equipment (KLA-Tencor Candela CS20);
[0184] The service life (Life Time) is measured by recording the maximum length of time that the polishing pad is continuously subjected to chemical mechanical polishing (CMP) testing until the polishing removal rate drops significantly.
[0185] The test results of the physical parameters and polishing performance of the rough polishing pads for SiC wafers prepared in Examples 1 to 4 and the rough polishing pads prepared in Comparative Examples 1 to 4 are shown in Table 1.
[0186] Table 1 Physical parameters and polishing performance test results of the rough polishing pads prepared in Examples 1 to 4 and Comparative Examples 1 to 4
[0187]
[0188] The test results of the physical parameters and polishing performance of the rough polishing pads of the above embodiments and comparative examples show that:
[0189] 1. Compared with Comparative Examples 1 to 2 (using a single wet resin), Examples 1 to 4 prepare a rough polishing pad by compounding a type A wet resin having a polyurethane-polyurea chain and a high hard segment content and a type B wet resin having a polyurethane chain and a low hard segment content. The rough polishing pad can effectively improve the surface flatness (reduced roughness) and defectivity (reduced number of defects), and can also improve its hardness, strength and wear resistance, while effectively maintaining a high removal rate, and the service life is not affected.
[0190] 2. Compared with Comparative Example 3, Examples 1 to 4 add silane coupling agent in the wet impregnation process, which can greatly improve the bonding and adhesion between PET fiber and wet resin. The wet resin and PET fiber are more tightly combined, and the prepared rough polishing pad has better wear resistance (reduced wear). The resin is not easy to fall off during the rough polishing process of the SiC wafer, thereby effectively improving its removal rate and service life.
[0191] 3. Compared with Comparative Example 4, Examples 1 to 4 add a composite antioxidant in the wet immersion process, and the rough polishing pads prepared therefrom can greatly improve the tolerance to the oxidants in the polishing solution, and can effectively slow down the corrosion of the rough polishing pads by the polishing solution, thereby effectively improving the corrosion resistance (increasing the corrosion resistance time) and service life of the SiC wafer in the rough polishing process.
[0192] The above contents are merely examples and illustrations of the structure of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A rough polishing pad for SiC wafer, characterized in that: It is prepared from the following components by weight: 500-1500 parts of A-type wet resin, 200-800 parts of B-type wet resin, 5-10 parts of aminosilane coupling agent, 5-10 parts of epoxysilane coupling agent, 1-5 parts of hindered phenol antioxidant, 1-5 parts of phosphite antioxidant, 600-1600 parts of diluent solvent, 150-160 parts of non-woven fabric, 300-330 parts of adhesive; The type A wet-process resin is a wet-process resin having polyurethane-polyurea chain segments and a hard segment content of 54.5% to 66.7%; the type B wet-process resin is a wet-process resin having polyurethane chain segments and a hard segment content of 35.1% to 45.8%.
2. The rough polishing pad for SiC wafer according to claim 1, characterized in that: The rough polishing pad for SiC wafer has a thickness of 1.2-1.4 mm, a hardness of 75-85 Shore A, and a compression ratio of 2%-5%; The viscosity of the type A wet-process resin at 25° C. is 100,000 to 120,000 mPa·S, and the number average molecular weight Mn is 80,000 to 100,000; The B-type wet-process resin has a viscosity of 80,000 to 100,000 mPa·S at 25° C. and a number average molecular weight Mn of 60,000 to 80,000.
3. The rough polishing pad for SiC wafer according to claim 2, characterized in that: The aminosilane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; The epoxysilane coupling agent is selected from at least one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3-(2,3-epoxypropoxy)propyltriethoxysilane.
4. The rough polishing pad for SiC wafer according to claim 2, characterized in that: The hindered phenol antioxidant is selected from at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; The phosphite antioxidant is selected from at least one of tris(2,4-di-tert-butyl)phenyl phosphite, triphenyl phosphite or tris(nonylphenol)phosphite.
5. The rough polishing pad for SiC wafer according to claim 2, characterized in that: The dilution solvent is selected from at least one of N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide; The nonwoven fabric is selected from PET needle-punched nonwoven fabric or PET spunlace nonwoven fabric, and its thickness is between 1.3 and 1.5 mm, and its gram weight is between 150 and 160 g / m 2 between. The back adhesive is selected from pressure-sensitive acrylic or silicone double-sided adhesive, and its thickness is between 100 and 200 μm.
6. The rough polishing pad for SiC wafer according to claim 1, characterized in that: The A-type wet-process resin is prepared from the following components in parts by weight: 150-200 parts of diisocyanate, 200-250 parts of polyether diol, 150-200 parts of aromatic diamine, 1-5 parts of chain terminator, and 500-1500 parts of diluent solvent.
7. The rough polishing pad for SiC wafer according to claim 6, characterized in that: The diisocyanate is selected from at least one of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 4,4'-diphenylmethane diisocyanate or 2,4'-diphenylmethane diisocyanate; The polyether diol is selected from at least one of polypropylene glycol, polytrimethylene ether glycol or polytetrahydrofuran diol; The aromatic diamine is selected from at least one of 4,4'-diamino-3,3'-dichlorodiphenylmethane, diethyltoluenediamine or 4,4'-methylenebis(3-chloro-2,6-diethylaniline); The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
8. The rough polishing pad for SiC wafer according to claim 6, characterized in that: The synthesis method of the A-type wet resin comprises the following steps: Prepolymerization reaction: dehydrating the polyether diol at 105-110° C. and negative pressure of 0.08-0.10 MPa for 1 hour, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer; Chain extension reaction: adding diluent solvent and aromatic diamine to the prepared prepolymer in sequence for chain extension, and maintaining the temperature between 80 and 90° C. for solution polymerization reaction for 4 to 6 hours; The reaction is terminated. When the polymerization reaction of the above system reaches a number average molecular weight Mn between 80,000 and 100,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a type A wet-process resin.
9. The rough polishing pad for SiC wafer according to claim 1, characterized in that: The B-type wet process resin is prepared from the following components in parts by weight: 250-300 parts of diisocyanate, 450-500 parts of polyester diol, 20-80 parts of small molecule diol, 1-3 parts of chain terminator, and 1000-2000 parts of diluent.
10. The rough polishing pad for SiC wafer according to claim 9, characterized in that: The diisocyanate is selected from at least one of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 4,4'-diphenylmethane diisocyanate or 2,4'-diphenylmethane diisocyanate; The polyester diol is selected from at least one of polycaprolactone diol and polycarbonate diol; The small molecule diol is selected from at least one of ethylene glycol, 1,4-butanediol or 1,3-propylene glycol; The chain terminator is selected from at least one of methanol, ethanol or isopropanol.
11. The rough polishing pad for SiC wafer according to claim 9, characterized in that: The synthesis method of the B-type wet resin comprises the following steps: Prepolymerization reaction: dehydrating the polyester diol at 110-115° C. and negative pressure of 0.08-0.10 MPa for 2 hours, adding diisocyanate to carry out bulk prepolymerization reaction at 80-90° C. for 2-3 hours to obtain an isocyanate-terminated prepolymer; Chain extension reaction: adding diluent solvent and small molecule diol to the prepared prepolymer in sequence for chain extension, and maintaining the solution polymerization reaction at 80-90°C for 4-6 hours; The reaction is terminated. When the polymerization reaction of the above system reaches a number average molecular weight Mn between 60,000 and 80,000, a chain terminator is added to terminate the reaction, and the material is discharged to obtain a B-type wet-process resin.
12. A method for preparing a rough polishing pad, used for preparing the rough polishing pad for SiC wafer according to any one of claims 1 to 11, characterized in that: The following steps are involved: Step 1: Impregnation slurry dispersion, add type A wet resin, type B wet resin, amino silane coupling agent, epoxy silane coupling agent, hindered phenol antioxidant, phosphite antioxidant and dilution solvent into a container, and disperse at a speed of 800-1000r / min for 2-3h until the mixture is evenly mixed; Step 2: Degassing the impregnation slurry, degassing the evenly dispersed impregnation slurry for 2 to 3 hours under a negative pressure of 0.08 to 0.10 MPa, and the viscosity of the impregnation slurry at 25° C. is 1000 to 3000 mPa·S; Step 3: impregnation and wet coagulation, the impregnation slurry and the non-woven fabric fiber are fully mixed to make the impregnation uniform, and placed in a DMF aqueous solution with a temperature of 25 to 45° C. and a concentration of 10% to 30% for wet coagulation; Step 4: Washing and drying to fix the solidified sample, place the solidified sample in deionized water at 40-60°C to clean the solvent, repeat more than 10 times until the sample solvent concentration is less than 1%, and place it at 100-120°C to dry for 4-6 hours to fix the sample; Step 5: Surface grinding and grooving: Grind the above-shaped sample with 150-400 grit sandpaper to make it smooth, remove the wet resin attached to the surface, and then perform grooving; Step 6: Back glue bonding and cutting, the above-mentioned grooved samples are bonded with back glue and cut into discs to obtain rough polishing pads for SiC wafers.
Citation Information
Patent Citations
Polishing pad
CN103402706A
Vinyl chloride-vinyl acetate resin modified polyurethane composite polishing pad and preparation method thereof
CN118744401A
Polishing pad
JP2004042189A
Chemical mechanical polishing pad
US20070275226A1